2020
DOI: 10.1002/smll.202000627
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Formation and Size‐Evolution Pathways of Thiolate‐Gold Nanoclusters in the CO‐Directed [Au25(SR)18] Synthesis

Abstract: An intermolecular association and decarboxylation mechanism is proposed to understand the experimental evidence of the stepwise 2e− hopping in the reductant‐assisted thiolate‐gold cluster synthesis. Based on the newly proposed intermolecular reaction mechanism, a total of 19 molecular‐like reaction equations are deduced to account for the bottom‐up formation of 2e−–8e− gold nanoclusters in the CO‐directed [Au25(SR)18]− synthesis. With these established reaction equations, atomic pathways of three prototype clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…For such a geometric structure, formation of a core–shell structure with Pd as the core and Au as the shell typically dose not occur. Although the chemical composition of the final product is affected by the reaction path, 63,64 this geometric factor appears to be largely related to the fact that Au 27 Pd(SPh t Bu) 20 and Au 26 Pd 2 (SPh t Bu) 20 were not formed in our experiments.…”
Section: Resultsmentioning
confidence: 81%
“…For such a geometric structure, formation of a core–shell structure with Pd as the core and Au as the shell typically dose not occur. Although the chemical composition of the final product is affected by the reaction path, 63,64 this geometric factor appears to be largely related to the fact that Au 27 Pd(SPh t Bu) 20 and Au 26 Pd 2 (SPh t Bu) 20 were not formed in our experiments.…”
Section: Resultsmentioning
confidence: 81%
“…Recently, our group proposed 18 stoichiometric equations to understand the 2e − hopping process in the bottom-up synthesis of the [Au 25 (SR) 18 ] − cluster. 18 The atomic pathway of formation of 2e − , 4e − , 6e − , and 8e − clusters as well as the conversion of facecentered cubic configuration [Au 23 (SR) 16 ] − to the icosahedral [Au 25 (SR) 18 ] − cluster was proposed. Our results indicated that a smaller size cluster can convert into a larger size cluster via a LaMer growth mechanism by carboxylation and decarboxylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that a smaller size cluster can convert into a larger size cluster via a LaMer growth mechanism by carboxylation and decarboxylation reactions. 18 Furthermore, based on the "2e − -unit decomposition" strategy, it was possible to deduce the intermediate species and their structures involved in the size conversion process from one cluster to another cluster. 18 In this study, we carried out systematic theoretical study on the seed-mediated growth mechanism of gold clusters from 8e − [Au 25 (SR) 18 ] − to 14e − Au 38 (SR) 24 and then to the 18e − A u 4 4 ( S R ) 2 6 c l u s t e r .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations